The Role of Antibodies Against the Crude Capsular Extract in the Immune Response of Porcine Alveolar Macrophages to In Vitro Infection of Various Serovars of Glaesserella (Haemophilus) parasuis - Matiašková, Katarína; Kavanová, Lenka; Kulich, Pavel; Gebauer, Jan; Nedbalcová, Kateřina; Kudláčková, Hana; Tesařík, Radek; Faldyna, Martin (Frontiers in immunology, 2021)
In Glässer's disease outbreaks, Glaesserella (Haemophilus) parasuis has to overcome the non-specific immune system in the lower respiratory tract, the alveolar macrophages. Here we showed that porcine alveolar macrophages (PAMs) were able to recognize and phagocyte G. parasuis with strain-to-strain variability despite the presence of the capsule in virulent (serovar 1, 5, 12) as well in avirulent strains (serovar 6 and 9). The capsule, outer membrane proteins, virulence-associated autotransporters, cytolethal distending toxins and many other proteins have been identified as virulence factors of this bacterium. Therefore, we immunized pigs with the crude capsular extract (cCE) from the virulent G. parasuis CAPM 6475 strain (serovar 5) and evaluated the role of the anti-cCE/post-vaccinal IgG in the immune response of PAMs to in vitro infection with various G. parasuis strains. We demonstrated the specific binding of the antibodies to the cCE by Western-blotting assay and immunoprecipitation as well as the specific binding to the strain CAPM 6475 in transmission electron microscopy. In the cCE, we identified several virulence-associated proteins that were immunoreactive with IgG isolated from sera of immunized pigs. Opsonization of G. parasuis strains by post-vaccinal IgG led to enhanced phagocytosis of G. parasuis by PAMs at the first two hours of infection. Moreover, opsonization increased the oxidative burst and expression/production of both pro- and anti-inflammatory cytokines. The neutralizing effects of these antibodies on the antioxidant mechanisms of G. parasuis may lead to attenuation of its virulence and pathogenicity in vivo. Together with opsonization of bacteria by these antibodies, the host may eliminate G. parasuis in the infection site more efficiently. Based on these results, the crude capsular extract is a vaccine candidate with immunogenic properties.
Keywords: kinetika; protilátky bakteriální; kultivované buňky; neutralizující protilátky; specificita protilátek; Phagocytosis; catalase; hemofilové infekce; alveolární makrofágy; reaktivní formy kyslíku; virulence; antioxidants; Haemophilus Infections; Macrophages, Alveolar; Serogroup; capsule; Sus scrofa; antigeny bakteriální; antibodies; bakteriální pouzdra; fagocytóza; Antigens, Bacterial; Antibodies, Neutralizing; Cells, Cultured; Reactive Oxygen Species; porcine alveolar macrophages; reactive oxygen species; Bacterial Capsules; zvířata; Haemophilus parasuis; Virulence; Antibodies, Bacterial; Kinetics; Antibody Specificity; Glaesserela parasuis; séroskupina; Animals